SAT0219 EFFICACY AND SAFETY OF TOCILIZUMAB IN GIANT CELL ARTERITIS INDEPENDENTLY OF THE INICIAL PREDNISONE DOSE. (June 2019) - Calderón-Goercke, Monica; Loricera, J.; Prieto-Peña, D.; Aldasoro, Vicente; Castañeda, Santos; Villa-Blanco, Ignacio; Humbría, Alicia; Moriano, Clara; Romero-Yuste, Susana; Narváez, J.; Gomez-Arango, Catalina; Perez-Pampín, Eva; et al.
Abstract : Background: Tocilizumab (TCZ) has been approved for the treatment of Giant Cell Arteritis (GCA). It showed to be effective to induce remission, prevent relapses and decrease the cumulative prednisone dose. However, the glucocorticoids are the mainstay in the acute treatment of GCA. Objectives: Our aim was to compare the efficacy and safety of the initial dose of prednisone at the onset of TCZ treatment. Methods: Retrospective, multicenter study on 134 patients with GCA in treatment with TCZ. We compared two subgroups of patients according to the initial dose of prednisone at TCZ onset. Clinical efficacy, analytical improvement and safety was studied. Results: We studied 134 patients (101 w/33 m) and made a comparative study between 2 groups: a) TCZ and ≤ 15 mg of prednisone; 68 (50.7%) cases, and b) TCZ and > 15 mg of prednisone, 66 (49, 3%) patients. It is summarized in TABLE 1 . It was no statistical significance according to age, sex and evolution time of disease. In the group receiving > 15 mg of prednisone, the patients presented more visual involvement (p<0.001) at TCZ onset. In terms of prolonged remission and relapses no significant difference was seen between both groups. The risk of presenting adverse effects (11.8% vs 36.4%) and severe infections (4.4% vs 19.7%) was related with the prednisone dose, being more frequent in the group with > 15 mg of prednisone (p=0.001 and p=0.006, respectively). TABLE 2 summarizes the infections of our patients. Conclusion: According with our results, we can conclude that TCZ is equally effective; in terms of prolonged remission and relapses, with doses ≤ 15 mg of prednisone at treatment onset. Being the most important data, the higher risk to develop adverse effects, as well as infections with higher doses of prednisone. References: [1] Proven A. Glucocorticoid therapy in giant cell arteritis: duration and adverse outcomes. Arthritis Rheum. 2003; 49:703-8. [2] Calderón-Goercke M. Tocilizumab in giant cell arteritis. Observational, open-label multicenter study of 134 patients in clinical practice. Semin Arthritis Rheum. 2019 Jan 5. pii: S0049-0172(18)30571-7. doi: 10.1016/j.semarthrit.2019.01.003. [Epub ahead of print] Disclosure of Interests: Monica Calderón-Goercke: None declared, J. Loricera: None declared, D. Prieto-Peña: None declared, Vicente Aldasoro: None declared, Santos Castañeda Consultant for: Amgen, BMS, Pfizer, Lilly, MSD, Roche, Sanofi, UCB, Ignacio Villa-Blanco: None declared, Alicia Humbría: None declared, Clara Moriano: None declared, Susana Romero-Yuste: None declared, J. Narváez Consultant for: Bristol-Myers Squibb, Catalina Gomez-Arango: None declared, Eva Perez-Pampín: None declared, Rafael Melero: None declared, Elena Becerra-Fernández: None declared, Marcelino Revenga: None declared, Noelia Alvarez-Rivas: None declared, Carles Galisteo: None declared, Francisca Sivera: None declared, Alejandro Olive: None declared, María Álvarez del Buergo: None declared, Luisa Marena Rojas: None declared, Carlos Fernández-López: None declared, Francisco Navarro: None declared, Enrique Raya: None declared, Eva Galindez: None declared, Beatriz Arca: None declared, Roser Solans-Laqué: None declared, Arantxa Conesa: None declared, Cristina Hidalgo: None declared, Carlos Vázquez: None declared, Jose Andrés Román-Ivorra: None declared, Pau Lluch: None declared, Sara Manrique Arija Speakers bureau: ABBvie, MSD, Janssen, Lillly, Roche, Pfyzer, Novartis., Paloma Vela-Casasempere Grant/research support from: UCB, Abbvie, Pfizer, Roche, Bristol-Myer-Squibb (another research, not BIOBADASER related), Consultant for: UCB, Lilly, Pfizer, Roche, Bristol-Myer-Squibb, Speakers bureau: Roche, UCB, MSD, Pfizer, GSK, BMS, Lilly, Eugenio de Miguel: None declared, Carmen Torres-Martín: None declared, Juan Carlos Nieto: None declared, Carmen Ordas-Calvo: None declared, Eva Salgado-Pérez: None declared, Cristina Luna-Gomez: None declared, Francisco J. Toyos Sáenz de Miera: None declared, Nagore Fernández-Llanio: None declared, Antonio García: None declared, Carmen Larena: None declared, Natalia Palmou-Fontana: None declared, Vanesa Calvo-Río: None declared, Carmen González-Vela: None declared, Alfonso Corrales: None declared, María Varela-García: None declared, Elena Aurrecoechea: None declared, Raquel Dos-Santos: None declared, Ángel García-Manzanares: None declared, Norberto Ortego: None declared, Sabela Fernández: None declared, Francisco Ortiz-Sanjuán: None declared, Montserrat Corteguera: None declared, J. Luis Hernández: None declared, Miguel A González-Gay Grant/research support from: Prof. MA Gonzalez-Gay received grants/research supports from Abbvie, MSD, Jansen and Roche., Speakers bureau: Consultation fees/participation in company sponsored speaker's bureau from Pfizer, Lilly, Sobi, Celgene, Novartis, Roche and Sanofi., Ricardo Blanco Grant/research support from: Abbvie, MSD, and Roche, Consultant for: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen, Speakers bureau: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen